2014
DOI: 10.1590/0074-0276130252
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A enhances indoleamine 2,3-dioxygenase expression by dendritic cells and subsequently impacts lymphocyte proliferation

Abstract: Dendritic cells (DCs) are antigen (Ag)-presenting cells that activate and stimulate effective immune responses by T cells, but can also act as negative regulators of these responses and thus play important roles in immune regulation. Pro-angiogenic vascular endothelial growth factor (VEGF) has been shown to cause defective DC differentiation and maturation. Previous studies have demonstrated that the addition of VEGF to DC cultures renders these cells weak stimulators of Ag-specific T cells due to the inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…Zhao et al [40] demonstrated that melanomas generate a site of immune privilege by driving DCs fatty acid oxidation via a Wnt5ab-catenin-PPAR-γ signaling pathway that culminates in the induction of IDO enzyme activity, and this study also showed that inhibiting this pathway reverses DCs tolerization and enhances anti-PD-1 antibody efficacy in a transgenic model of melanoma. In the hypoxic environment, Marti et al [41] found that Vascular endothelial growth factor (VEGF) increases the expression and activity of IDO in DCs, which has a suppressive effect on Ag-specific and mitogen-stimulated lymphocyte proliferation. The tight correlation existing between immune-infiltrate, angiogenesis and cancer progression and dissemination to distant sites and to nodal compartments is now being explored further [42].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [40] demonstrated that melanomas generate a site of immune privilege by driving DCs fatty acid oxidation via a Wnt5ab-catenin-PPAR-γ signaling pathway that culminates in the induction of IDO enzyme activity, and this study also showed that inhibiting this pathway reverses DCs tolerization and enhances anti-PD-1 antibody efficacy in a transgenic model of melanoma. In the hypoxic environment, Marti et al [41] found that Vascular endothelial growth factor (VEGF) increases the expression and activity of IDO in DCs, which has a suppressive effect on Ag-specific and mitogen-stimulated lymphocyte proliferation. The tight correlation existing between immune-infiltrate, angiogenesis and cancer progression and dissemination to distant sites and to nodal compartments is now being explored further [42].…”
Section: Discussionmentioning
confidence: 99%
“…Affecting functions of memory T cells in pro-inflammatory responses has also been described after VEGF stimulation [188] . VEGF also have an indirect immunosuppressive function on lymphocyte activation and proliferation by increasing IDO secretion from dendritic cells [189] . VEGF-A secreted by tumor cells is involved in immunosuppression via down regulation of the transcription factor NF-κB and as a result, there is an inhibition of dendritic cell maturation, trafficking and antigen presentation [190][191][192] .…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…However, mature DCs function to abrogate T cells by VEGF may depend on VEGFR2 activation [60]. Recently, Marti et al showed that VEGF can not only regulate DC maturation but also induce immunosuppressive phenotype through the production of IDO [61]. Although plasmacytoid DC (pDC) function in cancer remains unclear, Agudo et al recently reported the role of VEGF signaling in pDC maturation in lymphoid tissues, which is mediated through an miRNA, miR-126 [62].…”
Section: Vegf Regulates DC Maturation and Its Functionmentioning
confidence: 99%